Beyond al-Jarḥ wa at-Ta‘dīl: A Critical Study of the Narrators Accused of Lying in Sunan Ibn Mājah - Hartati; Khoirul Anam; Indal Abror; Ahmad ‘Ubaydi Hasbillah (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
Islamic scholars have endeavored to address the spread of unauthentic traditions transmitted by unreliable narrators. The science of al-Jarḥ wa al-Ta'dīl plays an important role in the study of hadith criticism as it helps determine whether the narrators are trustworthy or have a bad track record. In this context, Sunan Ibn Mājah has several narrators who have very bad reputations, and some of them are even known to have lied or fabricated traditions. This study investigates these narrators using the al-Jarḥ wa al-Ta'dīl approach. The sources of data are books on biographical dictionaries of narrators, books on fabricated traditions, and books on hadith commentaries. The study identified thirty-one narrators who were accused of lying in the name of the Prophet. Among these narrators was Ibn Mājah’s direct teacher, ‘Abd al-Wahāb b. al-Ḍaḥāk (245/859), from whom Ibn Mājah narrated six traditions. Meanwhile, the narrator with the most narrations is Jābir b. Yazīd al-Ju'fī (128/750), who has sixteen narrations. Therefore, it is important to be cautious in looking at the traditions in Sunan Ibn Mājah because some of the narrators are liars. Researchers should continue to apply al-Jarḥ wa al-Ta'dīl to maintain integrity and ensure that Muslims are protected from misleading traditions.